Penerapan Data Mining pada Tata Letak Buku Di Perpustakaan Sintong Bingei Pematangsiantar dengan Metode Apriori - Andini, Yulia; Hardinata, Jaya Tata; Purba, Yuegilion Pranayama (STIKOM Tunas Bangsa Pematangsiantar, 2022)
The library is a place that has a large collection of knowledge books, magazines and other media that are arranged or arranged in a certain way so that it is easy for users to use properly and well. In placing books in the library, books are placed according to the book category given the numbering. However, the placement of books has not been regulated by looking at the level of books that are often borrowed and many visitors find it difficult to find books that are often borrowed. So it is necessary to create a system using a priori data mining method to determine the pattern of book layout arrangement in the library, this system can help to make it easier to determine the layout of the book as needed. Based on the results of the implementation of RapidMiner, the highest combination pattern of library book layout is Pure Science and Social Sciences with 50% support and 86% confidence. General Works and Pure Science were obtained with 41% support and 83% confidence. Furthermore, Public Works and Social Sciences with 41% support and 83% confidence.